The Association of Low‐Penetrance Variants in DNA Repair Genes with Colorectal Cancer: A Systematic Review and Meta‐Analysis. Issue 7 (July 2017) - Aggarwal, Nikhil; Donald, Neil D; Malik, Salim; Selvendran, Subothini S; McPhail, Mark JW.; Monahan, Kevin J
Abstract : OBJECTIVES: : Approximately 35% of colorectal cancer (CRC) risk is attributable to heritable factors known hereditary syndromes, accounting for 6%. The remainder may be due to lower penetrance polymorphisms particularly of DNA repair genes. DNA repair pathways, including base excision repair (BER), nucleotide excision repair (NER), mismatch repair (MMR), direct reversal repair (DRR), and double‐strand break repair are complex, evolutionarily conserved, and critical in carcinogenesis. Germline mutations in these genes are associated with high‐penetrance CRC syndromes such as Lynch syndrome. However, the association of low‐penetrance polymorphisms of DNA repair genes with CRC risk remains unclear. METHODS: : A systematic literature review of PubMed, Embase, and HuGENet databases was conducted. Pre‐specified criteria determined study inclusion/exclusion. Per‐allele, pooled odds ratios disclosed the risk attributed to each variant. Heterogeneity was investigated by subgroup analyses for ethnicity and tumor location; funnel plots and Egger's test assessed publication bias. RESULTS: : Sixty‐one polymorphisms in 26 different DNA repair genes were identified. Meta‐analyses for 22 polymorphisms in 17 genes revealed that six polymorphisms were significantly associated with CRC risk within BER ( APE1, PARP1), NER ( ERCC5, XPC), double‐strand break (RAD18), and DRR (MGMT), but none within MMR. Subgroup analyses revealed significant association of OGG1 rs1052133 with rectal cancer risk. Egger's test revealed no publication bias. CONCLUSIONS: : Low‐penetrance polymorphisms in DNA repair genes alter susceptibility to CRC. Future studies should therefore analyze whole‐genome polymorphisms and any synergistic effects on CRC risk. TRANSLATIONAL IMPACT: : This knowledge may enhance CRC risk assessment and facilitate a more personalized approach to cancer prevention.